Sedation practices for routine gastrointestinal endoscopy: a systematic review of recommendations - Dossa, Fahima (BMC Gastroenterol, 2021)
BACKGROUND: Sedation is commonly used in gastrointestinal endoscopy; however, considerable variability in sedation practices has been reported. The objective of this review was to identify and synthesize existing recommendations on sedation practices for routine gastrointestinal endoscopy procedures. METHODS: We systematically reviewed guidelines and position statements identified through a search of PubMed, guidelines databases, and websites of relevant professional associations from January 1, 2005 to May 10, 2019. We included English-language guidelines/position statements with recommendations relating to sedation for adults undergoing routine gastrointestinal endoscopy. Documents with guidance only for complex endoscopic procedures were excluded. We extracted and synthesized recommendations relating to: 1) choice of sedatives, 2) sedation administration, 3) personnel responsible for monitoring sedated patients, 4) skills and training of individuals involved in sedation, and 5) equipment required for monitoring sedated patients. We assessed the quality of included documents using the Appraisal of Guidelines for Research & Evaluation (AGREE) II tool. RESULTS: We identified 19 guidelines and 7 position statements meeting inclusion criteria. Documents generally agreed that a single, trained registered nurse can administer moderate sedation, monitor the patient, and assist with brief, interruptible tasks. Documents also agreed on the routine use of pulse oximetry and blood pressure monitoring during endoscopy. However, recommendations relating to the drugs to be used for sedation, the healthcare personnel capable of administering propofol and monitoring patients sedated with propofol, and the need for capnography when monitoring sedated patients varied. Only 9 documents provided a grade or level of evidence in support of their recommendations. CONCLUSIONS: Recommendations for sedation practices in routine gastrointestinal endoscopy differ across guidelines/position statements and often lack supporting evidence with potential implications for patient safety and procedural efficiency.